Conservation Systems for Positive Net Ecosystem Carbon Balance in Semiarid Drylands. Issue 1 (1st July 2019) - Thapa, Vesh R.; Ghimire, Rajan; Duval, Benjamin D.; Marsalis, Mark A.
Abstract : Core Ideas: The soil organic C dynamics and net ecosystem C balance of five dryland cropping systems were compared. Conservation systems stored up to 15% more soil organic C than conventional system. Net ecosystem C balance was positive with cover cropping. Cover crops and conservation tillage are crucial for soil C storage in drylands. Biomass C inputs often limit agroecosystem C dynamics, nutrient cycling, and soil organic carbon (SOC) storage in semiarid drylands. This study evaluated SOC and net ecosystem carbon balance (NECB) of five cropping systems in the drylands of the Southern Great Plains. Cropping systems evaluated included corn ( Zea mays )–sorghum [ Sorghum bicolor (L.) Moench] rotation with conventional tillage without cover cropping (CTNC), strip tillage with and without cover cropping (STCC and STNC, respectively), and no tillage with and without cover cropping (NTCC and NTNC, respectively). After 4 yr of experimental tillage, we measured CO2 emissions, soil and soil surface air temperatures, soil moisture content, potentially mineralizable carbon (PMC), total SOC, total nitrogen (TN), and net primary productivity (NPP). Conservation systems (any treatments including no‐till, strip till, or cover crops) had 5 to 6°C lower soil temperature and 2.8 to 4.9°C lower soil surface air temperature and stored 2.3 to 3.9% more soil moisture content than CTNC. Conservation systems also stored 15.2% more SOC than CTNC. Cropping systems that integrated cover crops in the rotation (STCC and NTCC) had greater NPP and positive NECB. Regardless of tillage management, cover cropping had a greater NECB, including SOC (NECBSOC ) than CTNC. Reducing tillage and diversifying cropping systems through cover cropping can benefit semiarid dryland agroecosystems by increasing SOC storage and maintaining positive NECB.